The Madhyamaka Contribution to Skepticism - Dreyfus, Georges B. J. (International journal for the study of skepticism, 2022)
This paper examines the work of Nāgārjuna as interpreted by later Madhyamaka tradition, including the Tibetan Buddhist Tsongkhapa (1357–1419). It situates Madhyamaka skepticism in the context of Buddhist philosophy, Indian philosophy more generally, and Western equivalents. Find it broadly akin to Pyrrhonism, it argues that Madhyamaka skepticism still differs from its Greek equivalents in fundamental methodologies. Focusing on key hermeneutical principles like the two truths and those motivating the Svātantrika/Prāsaṅgika schism (i.e., whether followers of Nāgārjuna should offer positive arguments or should proceed on a purely “negative” basis), it argues that the Svātantrika commitment to mere conventional practice is robust and allows for a skepticism consistent with the scientific practices we must take seriously in the modern world. These findings are put forth as an illustration of what the Western tradition might gain by better understanding of non-Western philosophy.